Analytical Study of Indicators of Multiple Intelligences in the Design Unit in Art Education Course - Mowafaq Ali Alsaggar; Hadeel Ali AlAtoom (Deanship of Scientific Research (DSR), the University of Jordan, 2021)
This study aims to reveal the degree of availability of indicators of multiple intelligences in design unit in Art Education course for the three upper primary grades (eighth, ninth and tenth) and to identify the balance of indicators of these intelligences. An analytical descriptive approach was used in this study to analyze the content of the design unit. The analysis was conducted through a set of basic units of analysis (specific outcomes of each lesson, proposed teaching strategies and basic concepts, pictures and illustrations, and activities), in addition to following Gardner's multiple intelligence scales. The study reached many results, most notably the presence of a discrepancy in the degrees of frequency of indicators of multiple intelligences in the design unit for the three upper primary grades. It was found that visual intelligence was ranked first and in close proportions for the three grades within the design unit, while the rest of the intelligences were distributed in an unbalanced way. The study also found that the design unit is devoid of any indicators of musical intelligence, and this contradicts what the theory of multiple intelligences emphasized about the significance of balancing the distribution of intelligences.